Effect the Sequential and Random Methods to Developing the Performance of Some Defensive Skills for Handball Players of Babylon Governorate Clubs - Mohamed, Jasim Jabber; Hrebid, Nabeel Kadhim; Hussein, Ali Radhi Abdul (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2022)
The importance of the research was to identify the effect of the training curriculum in a random and sequential exercise method in developing the performance of some basic defensive skills for the handball players of Babylon Governorate clubs. This prompted the researchers to conduct the research through the use of sequential and random methods in developing the performance of the most important basic defensive skills for the players of the Babylon Governorate clubs in handball during the training program prepared for the purpose Knowing the most appropriate method and method in teaching this skill. While the objectives of the research were to identify the impact of the training curriculum in a random and sequential exercise method in developing the performance of some basic defensive skills for the handball players of the Babylon Governorate clubs. As well as knowing the most appropriate training in developing the performance of some basic skills for the handball players of the Babylon Governorate clubs. The researchers concluded that the learning methods used increased the excitement and enthusiasm of the players, which contributed to the development process. While the researchers recommend the necessity of diversification and change in the use of exercises when teaching and developing motor skills, they help learners to rush towards learning with enthusiasm and without boredom.